Is there a North-South divide in self-employment in England? - Burke, Andrew; FitzRoy, Felix R.; Nolan, Michael A. (Cranfield University, 2007)
Using decomposition analysis, the paper investigates why Northern England has fewer but higher performing self-employed individuals than the South. We find the causes are mainly structural differences rather than regional variation in individual characteristics. There are more self employed individuals in the South, but on average they create fewer jobs. Post compulsory education has a strong negative effect on the probability of self employment in the South, probably due to better employment opportunities there, but little influence in the North. Education has some positive effects on job creation by entrepreneurs in both regions. Aggregate studies may thus give misleading results.
Keywords: Self-employment; Job creation; North-South divide; Decomposition